2010
DOI: 10.1111/j.1526-4610.2010.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Starting a Triptan: Results From the American Migraine Prevalence and Prevention Study

Abstract: New use of triptans is low in the population. Because adequacy of care was not assessed, future studies should focus on investigating whether this low rate of triptan start is proper or if it reflects an unmet treatment need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…New use of triptans is also low in the general population. Results from the "American Migraine Prevalence and Prevention Study" showed that use of triptans is lower in patients aged 60 years, and that moderate and severe disability predicts triptan use [20]. A higher use of triptans during the acute migraine were detected in Spanish migraneurs, although they had a significant lower mean number of migraine attacks.…”
Section: Discussionmentioning
confidence: 98%
“…New use of triptans is also low in the general population. Results from the "American Migraine Prevalence and Prevention Study" showed that use of triptans is lower in patients aged 60 years, and that moderate and severe disability predicts triptan use [20]. A higher use of triptans during the acute migraine were detected in Spanish migraneurs, although they had a significant lower mean number of migraine attacks.…”
Section: Discussionmentioning
confidence: 98%
“…Prior population studies show that 20% of persons with migraine used acute prescription medications for treatment 18 . In a study of AMPP participant data from the 2005 survey, 20.3% of individuals with migraine used triptans 19 …”
Section: Discussionmentioning
confidence: 99%
“…Among participations who had recently consulted a health care professional for headache and had ever received a diagnosis, predictors of using an appropriate acute treatment included household income, MIDAS scores, and the MSSS. Another analyses of the 2005 AMPP database found that younger age, higher household income, having health insurance, higher headache‐related disability, and use of preventive medications predicted triptan use 19 . For persons with unmet need, despite appropriate acute treatment, a more comprehensive approach to management is required.…”
Section: Discussionmentioning
confidence: 99%
“…Headache specialists usually prefer to treat acute attacks of migraine with a migraine‐specific medication with the dose and route of administration that has a great likelihood of success for that particular patient. Triptans are currently the preferred class of medication prescribed for this aim . They are effective medications, available in many dosage forms and many are now generic; but, among patients receiving triptans, upwards of 40% do not have optimal responses and 20‐30% of them develop a recurrent migraine attack requiring either re‐dosing or a rescue medication .…”
Section: Clinical Implications Of Future Cgrp‐related Medicationsmentioning
confidence: 99%